IMPLEMENTASI NILAI-NILAI KEPEMIMPINAN SANTRI MA'HAD DARRUL MUWAHHID DALAM PERSPEKTIF KITAB IDZOTUN NASYIIN KARYA SYEIKH MUSTOFA AL-GHOLAYAINI - Nurdin; sonai, sodikin; Suminta (LP2M JAMIAT KHEIR, 2024)
The transformation of Islamic boarding school pesantren education in the digital era presents an interesting dynamic in efforts to integrate traditional values with the demands of modernity. This research explores the implementation of leadership values contained in the book Idzotun Nasyiin by Sheikh Mustofa Al-Gholayaini at Ma'had Darrul Muwahhid, a unique pesantren that accommodates the needs of young urban Muslim professionals and university students in Jakarta. Using a descriptive qualitative approach, this study involved 35 students 20 male and 15 female with data collection techniques through in-depth interviews, participatory observation, and document analysis. The results reveal significant success in integrating classical leadership values such as istiqlal independence, khidmah service, syaja'ah courage, shabr patience, syukr gratitude, and tsubut perseverance in the context of modern life. The students demonstrate progressive character transformation, capable of harmonizing spiritual aspects with their professional demands. The main differentiation lies in the adaptive approach to the educational system and the strong community climate that supports holistic student potential development. This research produces a contemporary pesantren development model that contributes significantly to the discourse on Islamic education modernization. These findings serve as valuable references for Islamic educational institutions in designing programs that are adaptive to the needs of the times while maintaining the fundamental values of pesantren in shaping a generation of Muslims who excel both spiritually and professionally. Keywords: Islamic Leadership Values, Idzotun Nasyiin Book, Student Islamic Boarding School, Professional Islamic Students.